2013
DOI: 10.1007/s00345-013-1172-6
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in diagnostic imaging of localized prostate cancer

Abstract: Among ultrasound-based techniques, real-time elastography and C-TRUS seem the most promising techniques. Multiparametric MRI appears to have advantages over conventional T2-weighted MRI in the detection of PCa. Despite these promising results, currently, no recommendation for the routine use of these novel imaging techniques can be made. Prospective studies defining the value of various imaging modalities are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…A total of 12 systematic reviews [11][12][13][14][15][16][17][18][19][20][21][22] were relevant and met the preplanned inclusion criteria; however, none of them covered both of the guideline objectives or used the same study selection criteria as ours. A total of 8663 original studies in English were identified and 15 were analyzed.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A total of 12 systematic reviews [11][12][13][14][15][16][17][18][19][20][21][22] were relevant and met the preplanned inclusion criteria; however, none of them covered both of the guideline objectives or used the same study selection criteria as ours. A total of 8663 original studies in English were identified and 15 were analyzed.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…But its availability, costs, and the possibility to repeat the examination whenever necessary make it an asset for the urologist. A number of techniques have been developed in order to improve the sensitivity and specificity of grey scale US and they have proven their advantages in terms of PCa detection rate and the guidance of prostate biopsy [15]. Multiparametric MRI has revolutionized the diagnostics of PCa and offered the possibility to perform a true targeted biopsy, but the costs of the investigation, the low volume centers, and the lack of specialists hinder its implementation [12].…”
Section: Discussionmentioning
confidence: 99%
“…The suspicion is raised by the presence of a hypoechoic area, but this appearance is characteristic only for about 60% of PCa. The rest of PCa nodules are isoechoic, therefore they are usually missedat US [15,16]. Furthermore, only 17-57% of the hypoechoic areas at greyscale US are diagnosed as malignant at biopsy [17].…”
Section: Conventional Transrectal Grey Scale Ultrasoundmentioning
confidence: 99%
“…In spite of the advances in prostate cancer (PCa) detection and treatment, PCa continues to be one of the leading causes of cancer-related mortality in men [1], with approximately 180,000 new cases diagnosed and 26,000 cancer-related deaths projected in the United States in 2016 [2]. Hence, the diagnostic accuracy is essential to early intervention regarding tumor progression and metastasis, leading to increasing opportunity for surgery and satisfied prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Most prostate neoplasms (about 60%-80%) are hypoechoic on grey-scale TRUS, whereas 30%-40% are isoechoic, and approximately 1.5% are hyper-echoic [2]. The sensitivity and specificity of ultrasound for PCa diagnosis vary considerably from 18% to 96% and from 46% to 91% [1]. Considering the effectiveness and drawbacks of ultrasound, to develop a new protocol is necessary.…”
Section: Introductionmentioning
confidence: 99%